Advanced strength and applied elasticity - Ugural, A. C. (Prentice Hall PTR, 2003)
This systematic exploration of real-world stress analysis has been completely revised and updated to reflect state-of-the-art methods and applications now in use throughout the fields of aeronautical, civil, and mechanical engineering and engineering mechanics. Distinguished by its exceptional visual interpretations of the solutions, it offers an in-depth coverage of the subjects for students and practicing engineers. The authors carefully balance comprehensive treatments of solid mechanics, elasticity, and computer-oriented numerical methods. In addition, a wide range of fully worked illustrative examples and an extensive problem sets-many taken directly from engineering practice-have been incorporated. Key additions to the Fourth Edition of this highly acclaimed textbook are materials dealing with failure theories, fracture mechanics, compound cylinders, numerical approaches, energy and variational methods, buckling of stepped columns, common shell types, and more. Contents include stress, strain and stress-strain relations, problems in elasticity, static and dynamic failure criteria, bending of beams and torsion of bars, finite difference and finite element methods, axisymmetrically loaded members, beams on elastic foundations, energy methods, elastic stability, plastic behavior of materials, stresses in plates and shells, and selected references to expose readers to the latest information in the field.